(untitled) - Egbert, Joy (London, 2015)
Beginning each chapter with reviewer comments, Writing Education Research is designed to help scholars understand both how to write effective research reports and how to get published. Practice exercises and resource lists in each chapter offer easy-to-access information about the review and publication process. A perfect accompaniment to standard research courses, this practical book demystifies the writing process for anyone looking to publish articles, chapters, or papers in education.
Giảng dạy môn Viết tiếng Anh
Keywords: Kỹ năng viết,Writing skills,Luận văn, học thuật,Dissertations, academic; Authorship